CONCEPT, DEFINITION AND CHARACTERISTICS OF THE MONEY LAUNDERING PHENOMENON - Georgieva Hadji Krsteski, Nataša (Journal of process management and new technologies, 2020)
Money laundering is becoming an increasingly pressing issue for the scientific and professional public. Financial crime, no matter what form it takes, has the sole motive or purpose of the perpetrators, the acquisition of illegal property by making very small efforts, and most often it is the exploitation or abuse of work responsibilities, function, duty or power.From the previous knowledge and previous researches, one gets the impression that this is a very current problem, which leaves negative consequences and traces in people's daily lives and of course interest in society for overcoming it. Today, we are witnessing numerous debates and lectures, ie activities undertaken by the organizations to overcome the situation. At the same time, it seems that the efforts made to eliminate the factors for the occurrence of the problem are insufficient, so while theoretical elaborations on the problem are being carried out, the pages of the newspapers are being filled and they are breaking news for all media.Experiences in the field of combating the phenomenon of money laundering and prevention so far, despite the huge efforts, show that the desired results have not been achieved. Such a thesis is confirmed by several arguments and statistics that go in the direction that not only has the number of this crime not decreased, but that it is increasing rapidly. But the “dark figure” of this crime is also worrying, with the abuse of bank officials in the process of preventing or investigating money laundering, the number of unsolved cases being high, the impact of corruption taking its toll.
Keywords: crime; money laundering; society; negative behavior; characteristics; typology